Research on the treatment efficiency of improved sequential batch integrated wastewater equipment - MA Haibo; MIAO Liyong; XIAO Bo; LIU Zhijie; JIANG Xiaoyu; RONG Yi; REN Wuang (Gongye shui chuli)
A modified sequencing batch integrated plant(MSBR) with A2O and SBR tandem process was constructed to treat actual domestic wastewater, the operational characteristics and treatment efficacy of the plant were investigated under the conditions of water volume fluctuation, intermittent interruptions, and water temperature changes, and its operational economics were comparatively analyzed. The results showed that COD, NH4+-N and TN removal rates under the two situations of intermittent and continuous water intake achieved more than 90%,all of which satisfied the standard of Class I-A, while TP met the standard of Class I-B. When the hydraulic retention time was decreased to 10.4 h, the removal rates of COD, NH4+-N, TP, and TN reached 82.4%, 88.3%, 97.1%, and 68.3%, and the removal rates of COD and NH4+-N subsequently met the standard of class A. The removal rates of COD, NH4+-N, TP, and TN in the effluent were 92.8%, 95.7%, 93.0% and 77.8% in the summer and 89.8%, 89.3%, 91.6% and 72.3% in the winter, respectively. COD, NH4+-N, and TN satisfied “Discharge standard of pollutants for municipal wastewater treatment plant”(GB 18918-2002) the class A standards, whereas TP met the class B standards. Comparative analysis with the existing process showed that MSBR had significantly higher COD and NH4+-N removal loads, and the total operation and maintenance costs was 0.67 yuan/t. With obvious economic advantages, it could provide potential technological and conceptual innovations for domestic sewage treatment and ecological environmental management.